Answer:
x = 1
Explanation:
Simplifying
7(x + 1) + -2 = 5(x + 1) + 2
Reorder the terms:
7(1 + x) + -2 = 5(x + 1) + 2
(1 * 7 + x * 7) + -2 = 5(x + 1) + 2
(7 + 7x) + -2 = 5(x + 1) + 2
Reorder the terms:
7 + -2 + 7x = 5(x + 1) + 2
Combine like terms: 7 + -2 = 5
5 + 7x = 5(x + 1) + 2
Reorder the terms:
5 + 7x = 5(1 + x) + 2
5 + 7x = (1 * 5 + x * 5) + 2
5 + 7x = (5 + 5x) + 2
Reorder the terms:
5 + 7x = 5 + 2 + 5x
Combine like terms: 5 + 2 = 7
5 + 7x = 7 + 5x
Solving
5 + 7x = 7 + 5x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-5x' to each side of the equation.
5 + 7x + -5x = 7 + 5x + -5x
Combine like terms: 7x + -5x = 2x
5 + 2x = 7 + 5x + -5x
Combine like terms: 5x + -5x = 0
5 + 2x = 7 + 0
5 + 2x = 7
Add '-5' to each side of the equation.
5 + -5 + 2x = 7 + -5
Combine like terms: 5 + -5 = 0
0 + 2x = 7 + -5
2x = 7 + -5
Combine like terms: 7 + -5 = 2
2x = 2
Divide each side by '2'.
x = 1
Simplifying
x = 1